TEX264 coordinates p97- and SPRTN-mediated resolution of topoisomerase 1-DNA adducts - John Fielden (Nature Portfolio, 2020)
Eukaryotic topoisomerase 1 (TOP1) regulates DNA topology to ensure efficient DNA replication and transcription. Here, the authors reveal insights into the molecular resolution of topoisomerase 1-DNA adducts by TEX264, p97 and SPRTN.